Kolaborasi dan Kerja Sama Pengelolaan Obyek Wisata Alam: Kendala dan Prospeknya di Era Otonomi Daerah - Abdul Kholiq Azhari (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2019)
Abstract Nature tourism as the embodiment of biodiversity, natural beauty, ecosystem, ecotourism, tropical forest ecosystem, and marine ecosystem. Nature tourism can also be located in towns and villages in the form of natural landscapes of parks, rivers, gardens, rice fields, botanical gardens, zoos, campus and others. The beauty and attraction of natural attractions, can provide benefits for tourists, if managed optimally. Creativity and participation of natural tourism management, supported by juridical aspect, institutional aspect, infrastructure, budget and apparatus are in the Era of Regional Autonomy. Regional autonomy encourages collaboration and cooperation in the management of natural tourism objects based on pardigma Reinventing Government and Good governance. Therefore, the policy of regional autonomy can reduce various obstacles of management of natural attractions in autonomous regions, so that the management of natural and quality tourism objects that can be realized in the present and future. Keywords: management, nature tourism, collaboration, regional autonomy